Determination of the Contact Resistivity of Screen-printed Al Contacts Formed by Laser Contact Opening. (April 2015) - Kranz, Christopher; Lim, Bianca; Baumann, Ulrike; Dullweber, Thorsten
Abstract: Next-generation industrial PERC solar cells typically include local laser contact opening (LCO) of a dielectric passivation layer stack at the rear side and subsequent full-area aluminum screen printing and firing. In this work we carry out a variation of the rear contact pitch of p -type passivated emitter and rear ( p -PERC) solar cells to determine the specific contact resistivity of the resulting line-shaped aluminium rear contacts to ρc < 5 mΩ cm 2 . We also use the transmission line method (TLM) to measure ρc on PERC-like test wafers and obtain a median value of 3 mΩ cm 2 . The determined ρc values below 5 mΩ cm 2 confirm recent similar studies and contradict a former publication. The main reason for the discrepancy between the literature values is an inaccurate modelling of the bulk spreading resistance contribution to the total series resistance of PERC solar cells.